Effects of Amaranthus hypochondriacus supplementation during gestation and lactation on the apparent total tract digestibility of nutrients, lactational feed intake, and litter performance in sows. Issue 5 (6th May 2021) - Xia, Jun; Chen, Linlin; Huang, Pengfei; Mou, Qi; Yang, Ying; Li, Jiaming; Xu, Minglang; Li, Jianzhong; Yang, Huansheng; Yin, Yulong
Abstract: The purpose of this study was to investigate the effects of Amaranthus   hypochondriacus (AH) inclusion in the diets of gestating and lactating sows on the lactational feed intake, nutrient digestibility, and growth performance of suckling piglets. During gestation, 40 multiparous Landrace sows were restrictively fed with either a control diet or a diet including 30% AH. Both diets had similar levels of digestible energy and crude protein, but the 30% AH diet had higher crude fibre levels than the control diet. After breeding, lactating sows were fed ad libitum with one of two isoenergetic and isonitrogenous diets, either a control diet or a diet containing 10% AH. In gestating sows, AH supplementation was found to be associated with decreased digestibility of crude protein and dry matter ( p  < .001), resulting in lesser backfat depth ( p  < .001). However, in lactating sows, AH supplementation had little effect on digestibility and milk composition; moreover, it increased the feed intake ( p  < .001) and decreased backfat loss ( p  < .001) in sows. On the 21st day of lactation, suckling piglets in AH group showed significantly greater average daily gains ( p  < .001), and average body weight and litter weight significantly increased compared with sows fed the control diet. In conclusion, AH‐supplementation increased lactational feed intake in sows and improved the growth performance of suckling piglets. Abstract : The feed intake of sows during lactation plays a major role in improving growth performance of suckling piglets. This study showed that feeding Amaranthus hypochondriacus during gestation and lactation increased lactation feed intake of sows and improved growth performance of pre‐weaning piglets. The mechanisms of these changes are still unknown, and more investigations are required to increase the understanding of interactions between diet composition and feed intake regulation of sows.